LEARNING PROCESS OF BIOLOGY THROUGH THE GUIDED DISCOVERY LEARNING BASED ON LOCAL EXCELLENCE ON THE SUBCONCEPT OF EUBACTERIA ROLE IN LIFE - SURATMI SURATMI; RIDA OKTORIDA KHASTINI; NUR LAILI FAUZIYAH (Sriwijaya University Learning and Education International Conference, 2016)
The purposes of this study were to determine learning process of biology through the guided discovery learning based local excellence on subconcepts eubacteria role in life and to determine the skills of the students process through the guided discovery learning based local excellence. The method used was a descriptive method. The population in this research was class of X of SMAN 13 Tangerang District. The sampling technique used in this study was purposive sampling. The sample was the class X.A of SMAN 13 Tangerang District consisted of 46 students. The data were collected by observations, questionnaires and skills process of science test. The results of this study showed that student responses during learning activities using guided discovery learning based local excellence on subconcepts eubacteria role in life was good with a percentage of 77.34%. The skills process of the students belong to the good categories with an average percentage of 82.52%.